The Analysis of Peanut Farming in Central Buton District - Yunus, Lukman; Zani, Munirwan (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
This study aims to determine the income and feasibility of peanut farming in Central Buton District. The research was conducted in Central Buton District in March - April 2020. The research population was 60 peanut farmers in Central Buton District. The sampling technique used was the census method, which was by taking the entire population as the research sample. Types and sources of research data were primary data and secondary data. Research data collection techniques used were direct interviews and literature studies. Research variables included were costs, fixed costs, total costs, prices, production, and revenues. The data were analyzed using the analysis of income and R/C ratio analysis. The results showed that peanut farming income in Central Buton District was IDR 702.548/season. Meanwhile, the R/C ratio coefficient was 3, which means that the peanut farming in Central Buton District is financially feasible to develop.